Conflits de temporalités dans les services : le cas des caisses automatiques - Sophie Bernard (Temporalités)
Cashiers and their clients are part of two different time frames, with conflicting conceptions of time. Clients are focused on their individual situation, in a sequential temporal regime and in the here-and-now, while the cashiers worry about ensuring a satisfactory service for all the recipients of their work, simultaneously, in a longer time frame. These conflicting representations depend on a relationship of service where one character is working and the other isn’t. According to the balance of power between the service provider and the recipient, both the time conflict and the service relationship can be very different. In order to bring this discrepancy to light, this paper focuses on the case of cashiers at automatic self-service checkout, in an asymetric relationship that favours the clients. The setup of these checkouts increases the participation of clients, puts the cashiers’s work in a simultaneous time frame, and reinforces the discrepancy. Eventhough it might not seem so, the automation of checkouts leads to an intensification of the cashiers’ workload. But as the clients can’t see it, they keep expecting a total availability from the cashiers. This misunderstanding leads to a tense situation between the characters, that brings to light and reinforces the structural antagonism of time between the cashiers and their clients.